Prevention of lupus nephritis development in NZB/NZW mice by selective blockade of CD28. Issue 8 (10th July 2017) - Laurent, Laetitia; Le Fur, Awena; Bloas, Rozenn Le; Néel, Mélanie; Mary, Caroline; Moreau, Anne; Poirier, Nicolas; Vanhove, Bernard; Fakhouri, Fadi
Abstract : In the NZB/NZW mouse lupus nephritis model, we demonstrated that selective blockade of CD28, by tipping the costimulation balance, prevented the development of the disease, mainly via an increase in the production of the immunomodulatory molecule IDO. Thus, CD28 blockade represents a potential treatment strategy in human systemic lupus erythematosus. Abstract : Systemic lupus erythematosus (SLE) is a chronic systemic inflammatory disease. Autoantibodies (autoAbs) against double‐stranded DNA (ds DNA), the hallmark of lupus, are produced and maintained by the interaction between auto‐reactive B cells and CD4 + T cells. This interplay is controlled by the CD28/CD80‐86/CTLA‐4 axis. Here we investigated whether selective blockade of CD28‐CD80/86 co‐stimulatory interactions abrogates lupus nephritis development in a murine model of SLE. To this aim, NZB/NZW F1 mice were treated for 3 months, either with an anti‐CD28 Fab' fragment or a control Fab'‐IgG. The effect of CD28 blockade on lupus nephritis onset, survival, production of anti‐ds DNA antibodies and costimulatory molecules was evaluated. CD28 blockade prevented the development of lupus nephritis and prolonged survival during the 3‐month treatment and 12 weeks after. Furthermore, the production of anti‐ds DNA autoAbs was decreased. Lastly, the protective effect of CD28 blockade was associated with increased intrarenal expression of the immunoregulatory molecule, Indoleamine 2, 3‐dioxygenase, of the co‐inhibitory receptor programmed cell‐Death – 1 (PD‐1) and of its ligand programmed death ligand ‐ 1 (PDL‐1).In conclusion, CD28 blockade prevented the development of lupus nephritis in NZB/NZW F1 mice. This immunomodulatory strategy is a promising candidate for SLE therapy in humans.